Testimonies referring to the movement of Túpac Amaru II (1784-1812) - Huertas, Lorenzo (1978)
The investigation of the social struggles in Huamanga that we began in 1969, continues from that moment and day after day new data appears that enrich our knowledge about the social conflicts in the region; for example, in 1971 we presented to the V Congress of American History a small contribution on the repercussion of the Túpac Amaru II movement in Huamanga, a work that was done taking as a reference the Acts of the Cabildo de Huamanga of the years 1780-1781 and also some lawsuits against peasants indirectly related to the Cusco movement. Later, we found another document that contained a trial against Pablo Challco and his family accused of inciting the people of Chungui to rebel against priests and corregidores and for "rekindling" the memory of the great rebel Túpac Amaru. With this interesting contribution again in 1976, a work was published in the anthology made by Flores Galindo. From the analysis of these and other documents on the history of the former bishopric of Huamanga -today the department of Ayacucho- I deduced the following considerations.